New strategies for sustainable fisheries management: A case study of Atlantic salmon - Morris,O; Barquín,J; Belgrano,A; Blanchard,J; Bull,C; Layer-Dobra,K; Lauridsen,R; O’Gorman,E; Guõbergsson,G; Woodward,G (The Grantham Institute, 2022)
This briefing paper considers the alarming declines in fish stocks in recent years, and how holistic, integrated approaches can help manage fish stocks within biologically sustainable limits. Using Atlantic salmon as a case study, the authors highlight the challenges facing fisheries management and conservation, and the implications for policy and management.